1978
DOI: 10.1038/icb.1978.30
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Damage and Dna Repair Induced in Human Fibroblasts by Uv and Cholesterol Oxide

Abstract: Sumniar>\ In luiniaii lilirolblasts. cholesU-rol oxide induced a similar degree of chrnnuwome damage (H-(i% of inetaplia.st's) and DNA repair synthesis (8-10^ of cells with lijjlitl>-lai)i'llL'd nuclei) iw low dtwes of ultraviolet litilit (UV), but did not produLc single-stratid DN.A breaks or UiN.A diuinijic detectable hy inhibition of th\inidiiie incnrpuratiini. f^hroniosoiiie aberrations were deteeted up to S week.s iifter treatment with cholesterol oxide and VW Cined treatments had almost additixe ell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Higher levels of cholesterol are associated with the presence of cholesterol 5a,6c~-epoxide and cholesterol 5f3,6[3-epoxide and their corresponding triol. These substances have been reported to induce sarcomas (38), transform embryo hamster and human lung cancer cell lines in vitro (39,40), and induce DNA damage in vitro (41). Sevanian and Peterson (40) have reported that cholesterol epoxides are direct-acting mutagens.…”
Section: Cholesterol and Cholesterol Epoxides In Breast Fluidmentioning
confidence: 98%
“…Higher levels of cholesterol are associated with the presence of cholesterol 5a,6c~-epoxide and cholesterol 5f3,6[3-epoxide and their corresponding triol. These substances have been reported to induce sarcomas (38), transform embryo hamster and human lung cancer cell lines in vitro (39,40), and induce DNA damage in vitro (41). Sevanian and Peterson (40) have reported that cholesterol epoxides are direct-acting mutagens.…”
Section: Cholesterol and Cholesterol Epoxides In Breast Fluidmentioning
confidence: 98%
“…Considerable attention has recently been devoted to cholesterol oxidation products as a result of toxicological studies attributing adverse biological activities to many of these compounds. Cholesterol-5or,6or-epoxide (wCE) has been associated with atherogenesis (Gray et al, 1971;Imai et al, 1976), carcinogenesis (Bischoff, 1969;Black and Lo, 1971;Black and Chan, 1976) and various other toxic effects (Blackburn et al, 1979;Kandutsch and Chen, 1978;Parsons and Goss, 1978). 7cx-Hydroxycholesterol, 7P-hydroxycholesterol and 7-ketocholesterol have also been shown to exhibit toxicological properties (Kandutsch and Che!, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Tbe origins oftbe human melanoma cell lines and fibroblasts and tests for .Mycoplasma have been described (Parsons c/j/.. 1974;Parsons and Goss, 1978). Tbeclonesof mouse melanoma (B-16), Lewis lung tumour (LLT) and methy!cholanthrene-inducedfibrosarcomas(MC-2 and JR-2) were kindly provided by Dr. J. W. Sheridan.…”
Section: Biological Materialsmentioning
confidence: 99%